Creative and Innovative Approached to the Science of Management, the IC² Management and Management Sciences Series, Number 5. - Manes, Rene P. (The Accounting Review, 1994)
Reviews the book `Creative and Innovative Approaches to the Science of Management,' by Yuji Ijiri.